New understanding on the reaction pathways of the polyacrylonitrile copolymer fiber pre-oxidation: online tracking by two-dimensional correlation FTIR spectroscopy. Issue 6 (8th January 2016) - Zhao, Jing; Zhang, Jihai; Zhou, Tao; Liu, Xifei; Yuan, Qiang; Zhang, Aiming
Abstract : FTIR spectroscopy in combination with scaling-MW2D and 2D correlation analysis is used to study the reaction pathways of polyacrylonitrile copolymer fibers pre-oxidation. Abstract : Polyacrylonitrile (PAN) copolymer fiber pre-oxidation has important influence on the final properties of carbon fibers. Understanding and tracking the reaction pathways of this pre-oxidation has great significance in guaranteeing the quality of the resulting carbon fibers. In this study, in situ FTIR spectroscopy in combination with scaling moving-window two-dimensional correlation spectroscopy (scaling-MW2D) and 2D correlation analysis was used to study the reaction pathways. In addition, DSC and 13 C solid-state NMR were used to assist in the determination and verification of chemical structures. Scaling-MW2D revealed that pre-oxidation consists of an initial process (A, 69–223 °C) and a main process (B, 223–309 °C). From the sequential order of 2D correlation analysis, more detailed pathways were obtained. The induced reaction of comonomer units took place in process A (69–223 °C). In process B (223–309 °C), the initial cyclic structures were first generated from the induced structure formed in process A. Then, these initial cyclic structures underwent a series of oxidations and subsequent isomerization. Subsequently, a large number of AN units were immediately involved in the main cyclization reaction, and some β-amino nitriles were produced. One new understanding obtained is that the initial cyclic structures after oxidation and isomerization are the real induced "nucleus" of the main cyclization reaction, and therefore oxygen in the air plays a key role in the main cyclization of PAN. The final step is the dehydrogenation reaction on the polycyclic structures at a high temperature.